The Role And Importance Of The Teacher In Teaching Music Subjects - Muminova, Muqaddas Risqulovna (International Conference on Global Trends and Innovations in Multidisciplinary Research, 2025)
This article comprehensively covers the role and importance of the teacher in teaching music subjects. The professional competence, methodological preparation, creativity, psychological approach of the teacher and his tasks in the formation of musical culture are analyzed on a scientific basis. The article also presents ideas about the possibilities of using modern technologies, the role of music in aesthetic education and the specific pedagogical functions of the teacher.